Spatial and Temporal Variation of Selected Water Quality Parameters in the Tanzanian Side of Lake Victoria - Makaka, R. R.; Misi, Shepherd N.; Masocha, Mhosisi; Kimwaga, Richard J. (Tanzania Journal of Engineering and Technology, 2022)
Lake Victoria ' s water quality is increasingly becoming under heavy pressure mainly due to land based activities and aerial inputs which are taking place within the basin. This study was carried out to assess the spatial, including vertical and temporal, variation of the water quality of Lake Victoria on the Tanzanian side. Historical water quality data for the period from 2000 to 2016 was collected. Temperature, pH, Dissolved Oxygen (DO) and Turbidity were selected for study since they are the mostly measured and monitored water quality parameters. Land use-land cover changes were analysed using ArcGIS. ILWIS 3.7 software was used to classify the land use and land cover for the years 2000, 2010 and 2014. MERIS was used to analyse the spatial variation. One-way ANOVA was employed to test the significant variation between different parameters. The results showed that, for the pelagic zone, the range of temperature, pH, DO, and turbidity were 22.8 oC-28.68 oC, 6.3-10.52, 3.42-10.21 mg/l, 1.0 NTU-15.8 NTU respectively. The corresponding values for the littoral zones were 22.3 oC-26.8 oC, 6.47-10.16, 3.99-8.6 mg/l, 1.3-347 NTU respectively. The ANOVA analysis results show that there was a significant variation of NO3(p<0.01). Temperature, pH and DO decreased with the lake depth to the bottom for both zones. For the littoral zone, a strong correlation was observed between temperature and depth, temperature and DO, and between temperature and pH with R2=0.6, p<0.03, R2=-0.78, p<0.01 and R2=0.96, p<0.01, respectively. The bare soil, urban settlements and farm land increased by 38.9%, 8.4% and 10.7% respectively from the year 2000 to 2014 on the Tanzanian side. This could have led to water quality changes. Water quality parameters varied significantly between pelagic and littoral zones. Littoral zones are mostly polluted and thus should be the priority pollution control intervention areas. Key words: Spatial-temporal variation, water quality, strong correlation, land use change.